Analisa Determinan Kesejahteraan Keuangan Keluarga Usia Pensiun di Kota Padang - Seprinaldo Ikhsan; Laela Susdiani (Fakultas Ekonomi Universitas Andalas, 2022)
This study aims to determine the effect of financial management practices, financial planning, financial stress, and asset ownership on the financial well-being of retired families in Padang City. The object of this study were 200 respondents, namely people in the city of Padang who have entered retirement age or the age of 56 years. The sampling technique is nonprobability sampling with criteria or characteristics of the same age as 56 years, entering retirement, domicile in the city of Padang. The method used is multiple linear regression. The data were processed using SPSS version 16. The results showed that financial management practices and financial planning had a positive effect on financial well-being, financial stress had a negative effect on financial well-being, while asset ownership had no effect on financial well-being.